Development of a Speaking Skills Assessment Rubric Through the English Reporting News Project for High School Students in Kampung Inggris Purbalingga - Nugraha, Novanda Alim Setya; Lustyantie, Ninuk; Murtadho , Fathiaty (Institut Agama Islam Negeri Palopo, 2025)
This study aims to develop a valid, reliable, and practical speaking skills assessment rubric in the context of project-based learning, specifically through the English Reporting News Project for senior high school students at Kampung Inggris Purbalingga. The research method used is research and development (R&D) with stages including needs analysis, rubric design, expert validation, limited trial, and data analysis using a Likert scale involving 30 students. The results show that the developed rubric accommodates five main aspects of speaking skills: fluency, pronunciation, grammar, vocabulary mastery, and communication ability. Reliability analysis yielded a Cronbach’s Alpha value of 0.83, indicating a high level of internal consistency. Assessment data indicate that vocabulary mastery and fluency have the highest average scores, while pronunciation remains the main challenge for students. Furthermore, the rubric received positive feedback from teachers and students regarding its practicality and clarity of use. This study recommends the use of the rubric as an effective evaluation tool in project-based speaking learning and further development, particularly focusing on pronunciation aspects. The findings contribute significantly to the development of communicative and contextual English language assessment in the Indonesian educational context.